(untitled) (Altre Modernità, 2014)
Susan Sontag’s probably most influencing work – her reflection on the metaphoric aura enveloping certain diseases – may be of some use in introducing my approach to David Peace’s narrative, with particular reference to the so called Tokyo Trilogy